ANALISIS STRATEGI PENGEMBANGAN KINERJA INSTITUSI DALAM RANGKA MENINGKATKAN DAYA SAING DI POLITEKNIK NEGERI JAKARTA - Zulkifli; Afifah, Laras; Purwoko, Bambang (SEKOLAH PASCASARJANA PRESS, 2021)
This research is about Analysis of Institutional Performance Development Strategy in the Framework of Increasing Competitiveness in Jakarta State Polytechnic. Jakarta State Polytechnic is one of 43 State Polytechnics under the Ministry of Education and Culture of the Republic of Indonesia. This research is a qualitative research with a problem approach through descriptive analysis. The focus of this research is to analyze the strategies that will be applied for the development of institutional performance in order to improve competitiveness in the Jakarta State Polytechnic by referring to the selected strategies resulting from data collection conducted by researchers based on the results of the analysis in terms of internal and external factors of the organization, SWOT analysis, TOWS, EFE, IFE, VRIO analysis, and Competitive Profile Matrix in order to improve institutional competitiveness. After the research object is known its quadrant position, a business strategy for the development of the Jakarta State Polytechnic will be prepared in 2020-2024. After the chosen strategy is obtained, then Key Performance Indicators are developed.